Social elites and new communication methods/information technologies: The digital divide - RONTOS, KOSTAS; NAGOPOULOS, NIKOS; TSAPALA, FLORA (Archives of Business Research, 2014)
The aim of this article is to examine the directions taken by not only social but transnational inequalities too, in the framework of information society, where trough the internet new means of communication and provision of information that have entered our lives in a determinative way, are developed. The main issue at stake is to define whether the opinion of technological determinism about the effect of new technologies in improving the position of societies through its universal use is verified in practice or if a new elite is created, that with more and better use of the new technologies maintains – if not deepens – social inequalities. In relation to the aforementioned and in this particular proposal, apart from the broadened accessibility chances and the increase of the percentage of new technology users in general, especially the distinct character of digital goods and the determining character, both of the way of using them and the quality of these goods in combination with the purpose and the environment of use, is examined.